Challenges and Opportunities of Islamic Economics in Facing Modern Economic Conservatism in Indonesia - Setyobudi, Reza Prabu (BUDAI: MULTIDISCIPLINARY JOURNAL OF ISLAMIC STUDIES, 2023)
Islamic economics is presented as an alternative that offers the principles of justice, sustainability, and balance in facing the conservatism of modern economics dominated by capitalism and socialism. This study aims to identify the main challenges faced by Islamic economics in Indonesia, such as lack of literacy, supporting infrastructure, and limited regulations, and explore opportunities to expand its application in the public and private sectors. With a qualitative approach based on literature review and policy analysis, this study finds that Islamic economics has great potential to create a just economic balance